A systematic review of metal foam and heat pipe enhancement in Latent Heat Thermal Energy Storage system. (10th December 2022) - Jaisatia Varthani, A.; Shasthri, S.; Baljit, S.; Kausalyah, V.
Abstract: Latent Heat Thermal Energy Storage (LHTES) system is a promising solution to increase the efficiencies of renewable energy by storing the additional energy produced during peak periods and releasing it during the energy sink period. However, the low thermal conductivity of the LHTES (PCM) system hinders its commercial adaptation. Applying a hybrid enhancement of heat pipe and metal foam has the potential to amplify the thermal performance of the LHTES system by combining heat pipe's efficient heat transfer capacity with metal foam's highly effective thermal conductivity capability. Bibliometric analyses were performed to provide an insight on publication evolution and trends of the heat pipe (HP) enhancement in LHTES (HP PCM), metal foam (MF) enhancement in LHTES (MF PCM), and hybrid of both heat pipe and metal foam enhancement in LHTES (HP-MF PCM). Then, a state-of-the-art review of HP PCM, MF PCM, and a detailed review of HP-MP PCM was carried out. The bibliometric analysis and review study was designed to examine the well-established field of research in HP PCM, and MF PCM, and use it to identify the gaps in research and potential studies in its promising hybrid, HP-MF PCM. A lack of research was noted in heat pipe design parameters study, thermal storage capacity studies, and experimental studies at high temperatures (>400 °C) in HP-MF PCM. The review points out the potential of enhancing the thermal performance in HP-MF PCM by applying temperature gradient optimization techniques and the prospect of HP-MF PCM application in various fields of study. Highlights: Bibliometric analysis of the HP, MF, and HP-MF enhancement in PCM. State-of-the-art review of HP and MF enhancement in PCM. Detailed review of HP-MF enhancement in PCM. Identification of research gaps and potential studies of HP-MF enhancement in PCM.